Allergen-specific immunotherapy in allergic rhinitis - V. V. Klimov; N. S. Koshkarova; V. S. Sviridova; A. V. Klimov (Бюллетень сибирской медицины, 2022)
The review focuses on allergen-specific immunotherapy (AIT), a treatment method for atopic diseases, including allergic rhinitis. The theoretical and practical basics, development prospects, indications and contraindications to AIT, peculiarities of AIT execution in allergic rhinitis, and tolerogenic effects of immunotherapy are considered. Advantages and disadvantages of each of the two preferable routes of allergen administration in AIT, subcutaneous and sublingual, are described. The main goals of further AIT advancement include shortening of treatment protocols with no significant loss of efficacy, creation of a safer adverse effect profile, and distribution of AIT in developing countries.